2003
DOI: 10.1023/b:brat.0000006333.93597.9d
|View full text |Cite
|
Sign up to set email alerts
|

Using the International 10-20 EEG System for Positioning of Transcranial Magnetic Stimulation

Abstract: Using the 10-20 system for TMS positioning is applicable at low cost and may reach desired cortex regions reliably on a larger scale level. For finer grained positioning, possible interindividual differences, and therefore the application of neuroimaging based methods, are to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
533
1
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 920 publications
(579 citation statements)
references
References 21 publications
12
533
1
5
Order By: Relevance
“…Finally, studies have demonstrated that GABA B IPSPs inhibit GABA A IPSPs, consistent with the finding that LICI inhibits SICI (Sanger et al, 2001). Therefore, our finding of a strong correlation between LICI, as indexed though (Herwig et al, 2003). (a) The black waveform represents cortical evoked activity in response to TS alone, while the dashed waveform represents cortical evoked activity following paired-pulse LICI paradigm using an interstimulus interval of 100 ms (ie, LICI 100 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Finally, studies have demonstrated that GABA B IPSPs inhibit GABA A IPSPs, consistent with the finding that LICI inhibits SICI (Sanger et al, 2001). Therefore, our finding of a strong correlation between LICI, as indexed though (Herwig et al, 2003). (a) The black waveform represents cortical evoked activity in response to TS alone, while the dashed waveform represents cortical evoked activity following paired-pulse LICI paradigm using an interstimulus interval of 100 ms (ie, LICI 100 ).…”
Section: Discussionsupporting
confidence: 88%
“…In experiment 1, we examined LICI in the motor cortex concomitantly by both EMG and EEG. The coil was placed at the optimal position for eliciting MEPs from the right abductor pollicis brevis muscle (APB) muscle, which typically corresponded to a region between FC3 and C3 electrodes (Herwig et al, 2003). In experiment 2, LICI was examined in the DLPFC by EEG only.…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…With one exception, the observed deviations were below 5 mm. The maximally observed deviation was 6.0 mm, which still compares favorably to, e.g., coil placement according to the EEG 10-20 system (12) or relative to the motor representation of finger muscles (13). However, it will depend upon the experimental question if this amount of accuracy is sufficient or not.…”
Section: Discussionmentioning
confidence: 62%
“…Included patients were given an identification number linked to a centralised computer-generated randomisation code determining real or sham stimulation condition. system for electroencephalography electrode placement [12]. The real stimulation intensity was determined as 110% of the individual resting motor threshold (MT) [22].…”
Section: Study Design and Participantsmentioning
confidence: 99%